Distinct functions of Egr gene family members in cognitive processes - Poirier, Roseline; Cheval, Hélène; Mailhes, Caroline; Garel, Sonia; Charnay, Patrick; Davis, Sabrina; Laroche, Serge (Frontiers in Neuroscience, 2008)
The different gene members of the Egr family of transcriptional regulators have often been considered to have related functions in brain, based on their co-expression in many cell-types and structures, the relatively high homology of the translated proteins and their ability to bind to the same consensus DNA binding sequence. Recent research, however, suggest this might not be the case. In this review, we focus on the current understanding of the functional roles of the different Egr family members in learning and memory. We briefly outline evidence from mutant mice that Egr1 is required specifically for the consolidation of long-term memory, while Egr3 is primarily essential for short-term memory. We also review our own recent findings from newly generated forebrain-specific conditional Egr2 mutant mice, which revealed that Egr2, as opposed to Egr1 and Egr3, is dispensable for several forms of learning and memory and on the contrary can act as an inhibitory constraint for certain cognitive functions. The studies reviewed here highlight the fact that Egr family members may have different, and in certain circumstances antagonistic functions in the adult brain.